Suppression of NLRP3 inflammasome orchestrates the protective efficacy of tiron against isoprenaline-induced myocardial injury - Abdelrahaman, Doaa; Habotta, Ola A.; Taher, Ehab S.; El-Ashry, Eman S.; Ibrahim, Iman; Abdeen, Ahmed; Ibrahim, Ateya M.; Ibrahim, Reham M.; Anwer, Hala; Mihaela, Ostan; Olga, Rada; Alwutayed, Khairiah M.; et al. (Frontiers in Pharmacology, 2024)
The major contribution of myocardial damage to global mortalities raises debate regarding the exploration of new therapeutic strategies for its treatment. Therefore, our study investigated the counteracting effect of tiron against isoprenaline (ISO)-mediated cardiac infarction in mice. Tiron was administered to mice for 7 days prior to two consecutive injections of ISO on days 8 and 9 of the treatment protocol. Tiron significantly reduced the levels of CK-MB, LDH, and AST in serum samples of ISO-challenged mice. A considerable increase in the cardiac antioxidant response was observed in tiron-treated mice, as indicated by depletion of MDA and enhancement of antioxidant activities. Furthermore, tiron induced a marked decrease in NLRP3, ASC, and caspase-1 levels accompanied by weak immune reactions of IL-1β, NF-κB, TLR4, and iNOS in the infarct cardiac tissues. Histopathological screening validated these variations observed in the cardiac specimens. Thus, tiron clearly mitigated the oxidative and inflammatory stress by repressing the NLRP3 inflammasome and the TLR4/NF-κB/iNOS signaling cascade.